2022
DOI: 10.1111/eci.13892
|View full text |Cite
|
Sign up to set email alerts
|

Coronary artery calcium score and its association with stroke: A systematic review and meta‐analysis

Abstract: Background The relationship between coronary artery calcium (CAC) score and incident stroke is controversial. Methods We conducted a systematic review of the literature evaluating CAC score and incident stroke. A search of MEDLINE and EMBASE was performed, and data were extracted from relevant studies. Statistical pooling with random‐effects meta‐analysis was undertaken to evaluate the risk of incident stroke with any CAC vs. no CAC, 1–100 CAC vs. no CAC, and >100 CAC vs. no CAC. Results Data from nine differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…Even in individuals without established CAD, CAC was predictive of cardiac events. A meta-analysis of 45 studies with 192,080 asymptomatic and 32,477 symptomatic patients followed for up to 11 years showed that CAC was associated with increased risk of major adverse cardiovascular and cerebrovascular events (MACE) as well as all-cause mortality [11,12]. In the Mediators of Atherosclerosis in South Asians Living in America (MASALA) study, the 10-year atherosclerotic cardiovascular disease risk in South Asians correlates with the CAC burden [13].…”
Section: Introductionmentioning
confidence: 99%
“…Even in individuals without established CAD, CAC was predictive of cardiac events. A meta-analysis of 45 studies with 192,080 asymptomatic and 32,477 symptomatic patients followed for up to 11 years showed that CAC was associated with increased risk of major adverse cardiovascular and cerebrovascular events (MACE) as well as all-cause mortality [11,12]. In the Mediators of Atherosclerosis in South Asians Living in America (MASALA) study, the 10-year atherosclerotic cardiovascular disease risk in South Asians correlates with the CAC burden [13].…”
Section: Introductionmentioning
confidence: 99%